Costs of early spondyloarthritis: estimates from the first 3 years of the DESIR cohort. Issue 1 (4th April 2016) - Harvard, Stephanie; Guh, Daphne; Bansback, Nick; Richette, Pascal; Dougados, Maxime; Anis, Aslam; Fautrel, Bruno
Abstract : Objectives: To value health resource utilisation and productivity losses in DESIR, a longitudinal French cohort of 708 patients with early spondyloarthritis (SpA) enrolled between 2007 and 2010, and identify factors associated with costs in the first 3 years of follow-up. Methods: Self-reported clinical data from DESIR and French public data were used to value health resource utilisation and productivity losses in 2013 Euros. Factors associated with costs, including and excluding biological drugs, were identified in generalised linear models using the generalised estimating equations algorithm to account for repeated observations over participants. Results: The mean (±SD) annual cost per patient was €5004±6870 in year 1, decreasing to €4961±7457 in year 3. Patients who never received a biologic had mean 3-year total costs of €4789±6022 compared to €38 206±19 829 among those who received a biologic. Factors associated with increased total costs were peripheral arthritis (rate ratio (RR) 1.19; 95% CI 1.04 to 1.37; p<0.0001), time on biologics (RR 1.23 per month; 1.21, 1.24; p<0.0001), and average BASFI score (RR 1.18/10 point increase; 1.15, 1.25; p<0.0001). Factors associated with increased costs excluding biologics were baseline age (RR 1.10 per 5 year increase; 1.05, 1.16; p<0.0001), peripheral arthritis (RR 1.20; 1.02, 1.40; p<0.0133), time on biologics (RR 1.04 per month; 1.02, 1.05; p<0.0001), and average BASDAI score (RR 1.21 per 10 point increase; 1.16, 1.25; p<0.0001). Conclusions: In addition to biologics, factors like age, peripheral arthritis and disease activity independently increase SpA-related costs. This study may serve as a benchmark for cost of illness among patients with early SpA in the biologic era.